RANCANG BANGUN SISTEM INFORMASI PENJUALAN BERBASIS WEB DENGAN METODE EXTREME PROGRAMMING PADA PT. DAE DUCK TEXTILE - Neng Risma; Siti Nur; Komarudin Komarudin (STMIK Mardira Indonesia, Bandung, 2021)
One of the activities that are often carried out in the company is sales activities. This activity did not escape problems, such as errors in recording data transactions that resulted in losses from the company and the slow presentation of information and the preparation of reports that were not yet possible to be presented at any time. The sales system used in this data collection is still using the Microsoft Excel application which makes the sales activities not integrated properly so that in every business process it does not run effectively. Therefore, the purpose of this sales system design is to produce a sales application that is able to manage the sales data to make it easier for the Sales Admin to make sales transactions. In this study, the system development method used is Extreme Programming with Unified Modeling Language development tools implemented using the Codeigneter Framework and MySQL for database processing. Meanwhile, the methods in the sales information system application are made using a subjective and chronological filling system to search for sales transaction data based on the subject and date of the transaction. This research produces a web-based sales information system that is able to assist companies in processing sales transactions and making sales reports. Keywords: Sale, Extreme Programming, Unified Modeling Language, MySQL.DOI: 10.5281/zenodo.5784140